Debranching of pea starch using pullulanase and ultrasonication synergistically to enhance slowly digestible and resistant starch. (1st December 2018) - Lu, Zhan-Hui; Belanger, Nicholas; Donner, Elizabeth; Liu, Qiang
Highlights: Synergistic effect obtained by simultaneous pullulanase and ultrasound debranching of pea starch. Debranching rate was significantly accelerated by ultrasonication. Linear glucan content of 73% was achieved by synergistic debranching for 6 h. Debranched starch had 25% thermally stable resistant starch, which was independent of cold storage. Debranched starch had 11–16% slowly digestible starch, depending on cold storage time. Abstract: Pullulanase (P) and ultrasonication (U) were simultaneously applied to debranch pea starch to enhance slowly digestible starch (SDS) and resistant starch (RS) fractions in the debranched pea starch (DPS). A synergistic debranching effect was found under conditions of pullulanase (40 npun/g) and ultrasonication (100% amplitude in pulse mode, 1 min on followed by 9 min off), which produced 73.5% linear glucans, 18% SDS and 26% RS in the resulting DPS-PU after 6 h of debranching. Even when autoclaving the DPS-PU at 118 °C for 30 min, following cooldown, 11% SDS and 25% RS were retained in the DPS-PU, compared with 0% SDS and 12% RS in autoclaved native pea starch. The SDS fraction in autoclaved DPS-PU further increased to 16% while the RS content remained constant during 14 days of cold storage. In summary, DPS-PU is high in linear glucans, low in starch digestibility and has a thermally stable RS fraction.